2020
DOI: 10.1088/2631-7990/ab61c5
|View full text |Cite
|
Sign up to set email alerts
|

A review of processing of Cu/C base plate composites for interfacial control and improved properties

Abstract: The increase in both power and packing densities in power electronic devices has led to an increase in the market demand for effective heat-dissipating materials with a high thermal conductivity and thermal expansion coefficient compatible with chip materials while still ensuring the reliability of the power modules. Metal matrix composites, especially copper matrix composites, containing carbon fibers, carbon nanofibers, or diamond are considered very promising as the next generation of thermal-management mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…The idea behind this work was to let nano-ThO 2 react with two different carbon sources (graphite and graphene oxide) at high temperature in an inert atmosphere, to obtain ThC 2 -carbon nanocomposites and to verify the retention of high SSA in the final material. Composites materials demonstrated 16 better thermal properties and thus are of interest for our application. In our previous collaborative work, graphene had the effect of improving thermal properties of uranium carbide–carbon composites 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The idea behind this work was to let nano-ThO 2 react with two different carbon sources (graphite and graphene oxide) at high temperature in an inert atmosphere, to obtain ThC 2 -carbon nanocomposites and to verify the retention of high SSA in the final material. Composites materials demonstrated 16 better thermal properties and thus are of interest for our application. In our previous collaborative work, graphene had the effect of improving thermal properties of uranium carbide–carbon composites 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The high thermal conductivity (~ 400 W/m•K) of pure copper (Cu) makes it an essential material for thermal management applications in numerous industries, such as microelectronic manufacturing, power plants, and aerospace [1][2][3][4][5]. However, the shape (i.e., surface area) of heat sinks plays a crucial role in heat dissipation, and due to the current fabrication limitation is often a simple geometry [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on CNTs have concentrated on the preparation [ 3 , 4 ], the optimization of the mechanical properties of CNTs composites [ 5 , 6 ] and the enhancement of the effectiveness of CNTs as capacitor electrode materials [ 7 ]. In recent years, studies have shown that high temperature annealing is an effective approach to improve the structure and thermal conductivity of carbon materials [ 8 , 9 ]. Chen et al [ 10 ] found that thermal treatment is capable of repairing the structure of graphene and making graphene sheets accumulate more regularly.…”
Section: Introductionmentioning
confidence: 99%